Delimitación de zonas de cangahua con sequía en los cantones Pujilí y Latacunga de la Provincia de Cotopaxi para la cuantificación de afectados y propuesta de recuperación de suelos en el periodo 2019 – 2020. - Lagua Lagua, Nelly Margarita (2020)
This research aimed to delimit the cangahua areas with drought in Pujilí and Latacunga cantons at Cotopaxi province to determine the quantification of affected and thus generate a proposal for soil recovery during the 2019-2020 period. So, the baseline was established in La Victoria, Alpamalag, Eloy Alfaro, November 11, and Poalo parishes, where the susceptibility to erosion and soils of cangahua with drought was determined thanks to the superposition of slope cartography, precipitation, climate, use, and vegetation cover, relating the quantification of the loss of productivity of the soils divided in the study area by parishes. The weighting of the factors was obtained by preparing different specific thematic maps obtained in the ArcGIS 10.5 software, guided by various cartography overlay methodologies such as (ICONA; ALBALADEJO; CORINE; PAP / RAC), using a multi-criteria analysis on topics of GIS with a weighting to each factor valued from 1 to 5. Resulting in 2 different levels of menace: very low or null and low representing 64.33%, 48.45% respectively; it was also possible to stipulate that the area to be recovered is 281.92 (ha) within the 5 parishes, with a total of 112 affected, where La Victoria parish is the one with the highest percentage to recover with 22.51%. Therefore, the soil recovery proposal is based on the mechanical clearing of cangahua soils, with the integration of organic matter that contributes to structure (Alfalfa, "Vicia," Barley). Additionally, a hydroretention proposal in the eroded, desertified, and Cangahua soils decreases the socio-economic and environmental impacts that may be generated to the nearby population.